Sarkozysm: New European and foreign policy into old French bottles? - Ulla Holm (Danish Institute for International Studies (DIIS), 2009)
When Nicolas Zarkozy became president in 2007 he proclaimed a break with the past: France was no longer automatically to go it alone as during de Gaulle's presidency, but was to be integrated fully into NATO. Instead of competing with the strongest power on earth, France - as well as the EU - should in the future to a larger extent align it self with the interests of Washington. Sarkozy also promised a more active French European policy, after years of neglect. 'France was once again back in Europa', he said. Two and a half years later - and halfway through Sarkozy's first presidential term - changes are hard to find. In spite of Sarkozy's many promises and his activism - or constant change of agendas as his critics call it - in reality he has continued the foreign and European policy of Charles de Gaulle and Francois Mitterand and only added very little himself, Ulla Holm writes in her new DIIS Working Paper Sarkozysm - New European and Foreign Policy into Old French Bottles? Even if France once again has been fully integrated into NATO and is a trusted ally of the United States there is no automatic alignment with Washington. France still strives towards a multi-polar world. And French European policy is still typically French. 'A European Europe', a multi-polar world and France as a visible actor in Europe and in international politics are still the guidelines for French European - and Foreign policy, says Ulla Hom.
Keywords: 330; Außenpolitik; Sicherheitspolitik; Frankreich